Long-term persistence of structured habitats: seagrass meadows as enduring hotspots of biodiversity and faunal stability - Hyman, A. Challen (Proc Biol Sci, 2019)
Ecological studies indicate that structurally complex habitats support elevated biodiversity, stability and resilience. The long-term persistence of structured habitats and their importance in maintaining biodiverse hotspots remain underexplored. We combined geohistorical data (dead mollusc assemblages, ‘DA’) and contemporary surveys (live mollusc assemblages, ‘LA’) to assess the persistence of local seagrass habitats over multi-centennial timescales and to evaluate whether they acted as long-term drivers of biodiversity, stability and resilience of associated fauna. We sampled structured seagrass meadows and open sandy bottoms along Florida's Gulf Coast. Results indicated that: (i) LA composition differed significantly between the two habitat types, (ii) LA from seagrass sites were characterized by significantly elevated local biodiversity and significantly higher spatial stability, (iii) DA composition differed significantly between the two habitat types, and (iv) fidelity between LA and DA was significantly greater for seagrass habitats. Contemporary results support the hypotheses that local biodiversity and spatial stability of marine benthos are both elevated in structured seagrass habitats. Geohistorical results suggest that structured habitats persist as local hotspots of elevated biodiversity and faunal stability over centennial-to-millennial timescales; indicating that habitat degradation and concomitant loss within structurally complex marine systems is a key driver of declining biodiversity and resilience.